Analisis Pengaruh Elektrolit NaCl Pada Baterai Aluminum - Udara Terhadap Tegangan dan Arus - Dominico Da Silva, Ricardo; , Firas Maulana; Kurniawan, ekki (Jurnal Serambi Engineering, 2025)
With the rapid development of technology, this will affect the increasing demand for electrical energy, where the use of electrical energy generally uses fossil-based electrical energy. Therefore, with the presence of aluminum-air batteries with its existing advantages including high energy density, abundant raw materials and environmentally friendly properties as an alternative source solution, if built on a large scale it could be used for remote areas. In this research, the first experiment is conducted without using solar panels and the second experiment is conducted with solar panels. The test results show that aluminum air batteries connected to solar panels are more effective in producing a large enough voltage and current with a mixture of a small NaCl electrolyte solution, namely with a composition of 24 grams of salt mixed with 1 liter of water, which can produce a battery output of 14.1 volts and a current of 19.1 mA for direct current. One factor that determines the effectiveness of the performance of aluminum-air batteries is the concentration of the electrolyte solution used.